Analisis Mutu Pascapanen Melon (Cucumis melo L.) Kultivar Glamour Sakata Selama Penyimpanan - Amalya Nurul Khairi; Affan Fajar Falah; Agung Putra Pamungkas (CHEMICA: Jurnal Teknik Kimia, 2017)
The aims of this study are to observe the postharvest effect of storage and traditional marketâ€™s material handling on the quality of melon fruit Sakata cultivar. The physical qualities of melon fruit been observed were weight (measured by a scale), diameter and length (by sliding range), also fruit peel and flesh (with Zwick Type Universal Testing Machine DO-FB0.5TS). Chemical qualities of Sakata melon been observed were water content (thermogravimetric), Â°Brix sucrose (refractometer ABBE), pH (pH-meter), total carotene, total acid, and vitamin C with destructive methods.Storaging melon with traditional market method resulted in decreasing the value of physical parameters and increasing chemical parameters. Sakata melon softened during storage with fruit peel texture values was 6.45-8.07 N and fruit flesh texture was 1.4-2.06 N. The weight loss of Sakata melon was 0.06-0.25 kg, diameter dropped 0.0-0.6 cm, and length dropped 0.1- 0.5 cm during storage. Water content decreased from 92.84% to 91.19%. Sucrose content increase with values of 5.74-7.7 oBrix. Vitamin C levels showed a low and fluctuating value, 14.52-19.91 mg/100g. The melon fruit was slightly acidic with pH ranging from 6.2-6.96 and the total acid increased from 0.16 mg ek/100 g on the initial day to 0.31 mg ek/100 g on the eleventh day of storage. The total carotene content of melons ranged between 4.23-5.64 mg/100 g and indicated the flesh color of melon was getting more orange during storage.